Tanggung Jawab Siswa Dalam Pembelajaran Matematika SMA - Hastuti, Desi Dwi; Sutama, S.; Fuadi, Djalal (Universitas Muhammadiyah Surakarta, 2018)
This study aims to describe the forms, characteristics, and consequences of studentresponsibility in learning mathematics. This research is a qualitative research withethnography design. Techniques of collecting data using interviews, observation, anddocumentation. Data analysis techniques use interactive model analysis. The resultsof this study: 1) The forms of student responsibility in learning mathematics in highschool such as responsibility as individuals, religious people, students, and citizens.Student responsibilities collect the task thoroughly and follow the learning math well. Subject teachers assess the competence of knowledge and skills. BK teachers and religious teachers assess the competence of spiritual and social attitudes. 2) The characteristics of student responsibility in learning mathematics in high school done by completing the task well, ready to bear the burden and bear the risk, keeping promises, and can feel the difficulties of others. By following the extracurricular, students learn responsibility for the task. The teacher reminded the task and made a bill for who has not collected the task. 3) The consequences of student responsibility in high school mathematics have some advantages such as being able to help themselves, be effective in helping others, and be trustworthy. Cooperative learning can increase interaction among students and help each other in completing the task.